The Gift - Brunstetter, Wanda E (Uhrichsville, Ohio Shiloh Run Press an imprint of Barbour Publishing, Inc., 2015)
Having decided never to marry, Adam Beachy is nevertheless forced to take up the role of father figure for his young nieces when tragedy strikes, and sees in Leah Mast a practical spouse who can help, in spite of her practice of reflexology, which he finds ridiculous.
Keywords: Amish -- Fiction; Reflexology (Therapy) -- Fiction; Love stories